Microheater-integrated zinc oxide nanowire microfluidic device for hybridization-based detection of target single-stranded DNA. (1st April 2021) - Takahashi, Hiromi; Yasui, Takao; Kashida, Hiromu; Makino, Koki; Shinjo, Keiko; Liu, Quanli; Shimada, Taisuke; Rahong, Sakon; Kaji, Noritada; Asanuma, Hiroyuki; Baba, Yoshinobu
Abstract: Detection of cell-free DNA (cfDNA) has an impact on DNA analysis in liquid biopsies. However, current strategies to detect cfDNA have limitations that should be overcome, such as having low sensitivity and requiring much time and a specialized instrument. Thus, non-invasive and rapid detection tools are needed for disease prevention and early-stage treatment. Here we developed a device having a microheater integrated with zinc oxide nanowires (microheater-ZnO-NWs) to detect target single-stranded DNAs (ssDNAs) based on DNA probe hybridization. We confirmed experimentally that our device realized in-situ annealed DNA probes by which we subsequently detected target ssDNAs. We envision that this device can be utilized for fundamental studies related to nanobiodevice-based DNA detection.